2016
DOI: 10.2527/jas.2016-0503
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of including methane measurements in selection strategies

Abstract: Estimates of genetic/phenotypic covariances and economic values for slaughter weight, growth, feed intake and efficiency, and three potential methane traits were compiled to explore the effect of incorporating methane measurements in breeding objectives for cattle and meat sheep. The cost of methane emissions was assumed to be zero (scenario A), A$476/t (based on A$14/t CO equivalent and methane's 100-yr global warming potential [GWP] of 34; scenario B), or A$2,580/t (A$30/t CO equivalent combined with methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This was despite animals in LH1 generally being heavier. With LW being a key determinant of MER M (Touchberry and Lush 1950), enteric CH 4 being positively correlated with feed intake (Molano and Clark 2008) and voluntary intake being positively correlated with LW (Robinson and Oddy 2016), it would be expected that differences in calculated EF would align with observed LW differences across the AEZs. That this was not so can probably be attributed to a combination of the observed differences among zones in LW flux and locomotion, plus small differences among zones in average DMD, along with the assumption that CH 4 yield is a constant fraction of DM in forages, unrelated to digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…This was despite animals in LH1 generally being heavier. With LW being a key determinant of MER M (Touchberry and Lush 1950), enteric CH 4 being positively correlated with feed intake (Molano and Clark 2008) and voluntary intake being positively correlated with LW (Robinson and Oddy 2016), it would be expected that differences in calculated EF would align with observed LW differences across the AEZs. That this was not so can probably be attributed to a combination of the observed differences among zones in LW flux and locomotion, plus small differences among zones in average DMD, along with the assumption that CH 4 yield is a constant fraction of DM in forages, unrelated to digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic improvement of gas production is one way to get permanent and continuous reductions in CH 4 and simultaneously potentially improve efficiency. Robinson and Oddy (2016) found that including CH 4 into a breeding index will improve profit because of its high genetic relationship with feed intake, particularly when feed intake is not measured. Therefore, the high economic value of intake and the strong genetic correlation between intake and CH 4 , CO 2 , and O 2 could make these traits very important.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach is that of identifying individuals within the population who possess the desired phenotype, then selecting for those animals. In the case of the LMP, it needs to be considered that: (1) the technical requirements for identifying and testing animals are prodigious; (2) the differences between identified LMY and HMY animals are only in the region of 12-15% (Goopy et al 2014;Kittelmann et al 2014) and there is no evidence that this will be increased through trait selection; and (3) there is little if any, economic benefit to be gained by farmers in selecting for LMP under prevailing economic conditions (Robinson and Oddy 2016). Further, Eckard et al (2010) has warned that even though genetic selection for LMP animals is theoretically possible, the rate of genetic gain for the trait will necessarily be low in any multi-trait breeding program.…”
Section: Creating the Lmp Ruminantmentioning
confidence: 99%